(3efgL Ydej h JWHjb Yedjs - (3SejQ(B, (3GdNWjHs ((3GdEScfOQjI(B:s (3efTCI GdeYGQa(B,s, 2005)
(3OhQ EOGQI GdeNGWQ h adSaI GdeNGWQ h SjGSJgG h HYV GdeHGOF GdGSGSjI ddQbGHI GdaYGdI habG deJWdHGJ H```GRd h OhQ GdeDSSGJ GdOhdjI aj NaV GdeNGWQ h Cge GdJMOjGJ GdJj JhGLg GdHfhc h GOGQI GdGUhd h GdNUhe HZQV GdMO ef GdeNGWQ , CfhGY GdeNGWQ h HYV eDTQGJ bjGSgG h GdeNGWQ GdGFJeGfjI h GdeNGWQ GdeUQajI h CNjQG Cge GdJMOjGJ h GdeNGWQ GdJj JhGLg GdHfhc GdGSdGejI aj VhA GdJWhQGJ GdeUQajI GdMOjKI h ebQQGJ dLfI H``GRd h eDTQGJ bjGS eOi SdGeI COGA GdHfc(B.s
Keywords: (3GdCReGJs; (3GdGOGQIs; (3GdHfhcs